2011
DOI: 10.1098/rsif.2011.0009
|View full text |Cite
|
Sign up to set email alerts
|

Novel use of biodegradable casein conduits for guided peripheral nerve regeneration

Abstract: Recent advances in nerve repair technology have focused on finding more biocompatible, nontoxic materials to imitate natural peripheral nerve components. In this study, casein protein cross-linked with naturally occurring genipin (genipin-cross-linked casein (GCC)) was used for the first time to make a biodegradable conduit for peripheral nerve repair. The GCC conduit was dark blue in appearance with a concentric and round lumen. Water uptake, contact angle and mechanical tests indicated that the conduit had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
0
13
1
1
Order By: Relevance
“…Still these moderately hydrophobic contact angles were reported to be suitable for cell attachment and growth . In one such study, genipin crosslinked casein (GCC) conduit with a contact angle of 59.0 ° ± 4.5° led to 100% regeneration of sciatic nerves . PCL/SIS fibers with a contact angle of 85 o prepared by Hong and Kim were reported to be quite suitable for cell attachment and nerve regeneration.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Still these moderately hydrophobic contact angles were reported to be suitable for cell attachment and growth . In one such study, genipin crosslinked casein (GCC) conduit with a contact angle of 59.0 ° ± 4.5° led to 100% regeneration of sciatic nerves . PCL/SIS fibers with a contact angle of 85 o prepared by Hong and Kim were reported to be quite suitable for cell attachment and nerve regeneration.…”
Section: Resultscontrasting
confidence: 59%
“…It is more relevant because the conduit constructed in this study was initially free of cells and thus it was more appropriate to compare our results with those of the decellularized nerve. In another study the UTS of genipin crosslinked casein (GCC) conduit was found to be 0.17 ± 0.03 MPa, a value 10‐fold lower than those obtained in the current study . They concluded that the strength of their conduit was enough to resist the muscular contraction during sciatic nerve regeneration and support of axonal growth, and therefore the pHEMA membrane of the current study is suitable for use as a nerve guide even without mwCNT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the development of several surgical techniques15, new bridging materials16171819, and therapies2021222324, the autologous nerve graft is still the “gold standard” in long peripheral nerve gap reconstruction. Although there are some disadvantages to the procedure, such as a lack of autologous nerve sources or feeling obstacles for providing area during surgery, the autologous nerve graft is closest to the normal physiological structure and function when the above-noted difficulties can be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral nerve regeneration represents a series of highly specialized processes of healing when considered on a cellular level. Numerous investigators have bridged the stumps of a transected peripheral nerve by inserting them in conduits fabricated from a large variety of materials, either biological or artificial [14]. These nerve-bridging conduits provide a means for studying the nerve regenerative processes under controlled experimental conditions.…”
Section: Introductionmentioning
confidence: 99%